Sustainable Farming as Counterbalance: Revitalizing Pomponangi Farmer Group in Mining and Industrial Park-Dominated Regions - Chrisma Virginia; Harry Cahyono; Oktsyavitto Adhitya Nugroho; Irwanto Irwanto (Journal of World Science, 2025)
This study aims to evaluate the effectiveness of the "Harmoni Makarti" Corporate Social Responsibility (CSR) program, initiated by Hengjaya Mine, in revitalizing the Pomponangi farmer group through the introduction of sustainable farming practices as a counterbalance to industrial dominance. The research employed a quasi-experimental Difference-in-Differences (DiD) approach to analyze changes in land use, crop diversification, production costs, and farmer income. Data were collected through surveys, soil quality measurements, field observations, and analysis of farmer group records. Statistical analysis, including paired t-tests, was used to measure the program's impact. The intervention yielded significant positive outcomes. The program successfully secured farmland tenure, slowing conversion rates. It reduced average production costs by 21% (Rp 195 per kg) through the adoption of organic fertilizers and pesticides. Crop diversification increased from 4 to 10 types, leading to a 164% surge in average annual farmer income (from Rp 23.55 million to Rp 62.25 million). Furthermore, the establishment of market linkages with a local enterprise (BUMDES) generated an additional Rp 30.35 million in weekly revenue. The program also achieved a high Community Satisfaction Index score of 85.31. The "Harmoni Makarti" program demonstrates that well-designed CSR initiatives can effectively empower local farmer groups, promote sustainable agriculture, and enhance economic resilience in regions dominated by extractive industries. The findings suggest that such a model of corporate-community partnership is replicable and offers a viable strategy for achieving balanced regional development.